Evaluating the Accuracy of Self-Ratings of Language in Adults with Aphasia and Non-Brain Injured Adults: A Pilot Study - Arnett, Sarah; Mozeiko, Jennifer (Seminars in Speech and Language, 2022)
Rating scales are frequently used in research and clinical practice with people with aphasia (PWA) to characterize communication in the home environment. However, it remains unclear whether responses provided on rating scales accurately reflect the communication that occurs. We aim to evaluate the accuracy of PWA's self-perceptions of verbal language use as measured by a rating scale and determine whether this accuracy is different from that of non–brain-injured (NBI) participants. Four PWA and four NBI participants completed a rating scale estimating their amount of verbal language production as compared with their communication partner. Audio recordings from participants' home environments were analyzed for proportion of words and conversational turns contributed by the participant, which were compared with rating scale estimates. Perceptions of verbal language output among both PWA and NBI participants showed variable accuracy, with discrepancies between estimates and objective data across both groups. The reliability of rating scales in quantifying language output appears questionable, suggesting they may not accurately represent naturalistic language environments of PWA. Additional research with larger sample sizes is warranted to investigate whether this trend is consistent across a larger population of individuals with aphasia.
Keywords: aphasia; rating scales; home environment; self-perception